2020
DOI: 10.3390/ijerph17186693
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Problem Gambling in Elite Athletes during COVID-19 Restrictions—A Web Survey in Top Leagues of Three Sports during the Pandemic

Abstract: COVID-19 and lockdown strategies may affect mental health and addictive behavior differently in the population, and elite athletes are among the professions clearly affected by the pandemic. This study in top elite athletes aimed to study current perceived psychological influence from COVID-19 and symptoms of depression, anxiety and changes in alcohol drinking, gambling behavior and problem gambling in the midst of the COVID-19 lockdown. This web survey included athletes in top leagues of soccer, ice hockey an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
102
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 42 publications
13
102
0
11
Order By: Relevance
“…Pathological gambling is more common in males in the general population, although gender differences in prevalence may have further narrowed in the past few years [21,22]. A study by Hakansson on athletes during the COVID-19 period reported that gambling problems were clearly more common in males, and females did not even have moderate risk or problem gambling issues [23]. Similar to the literature, our study found that male participants had higher rates of gambling habits than female participants.…”
Section: Discussionsupporting
confidence: 85%
“…Pathological gambling is more common in males in the general population, although gender differences in prevalence may have further narrowed in the past few years [21,22]. A study by Hakansson on athletes during the COVID-19 period reported that gambling problems were clearly more common in males, and females did not even have moderate risk or problem gambling issues [23]. Similar to the literature, our study found that male participants had higher rates of gambling habits than female participants.…”
Section: Discussionsupporting
confidence: 85%
“…In a recent study, about half of the studied student sample reported that their gaming behavior had increased during the COVID-19 lockdown period and that gaming behavior was associated with examination-related stress (56). COVID-19 distress was also associated with elevated smartphone use (57), problematic gambling (58,59) and Internet use (60).…”
Section: Psychological Consequences Of Covid-19 On Individuals With Amentioning
confidence: 99%
“…Moreover, increased activity was associated with better mental health and wellbeing in the inactive population. A Swedish study showed that 72% of female and 40% of male elite athletes who responded to a survey reported that they were feeling psychologically worse during the pandemic [ 9 ]. However, the perceived impact on patterns of physical activity in the more general Swedish population has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%